2004
DOI: 10.1515/epoly.2004.4.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Reversible addition fragmentation chain transfer (RAFT) polymerization of styrene in fluid CO2

Abstract: Reversible addition fragmentation chain transfer (RAFT) polymerizations of styrene in fluid CO 2 have been carried out at 80°C and 300 bar using cumyl dithiobenzoate as the controlling agent in the concentration range of 3.5·10 -3 to 2.1·10 -2 mol/L. This is the first report on RAFT polymerization in fluid CO 2 . The polymerization rates were retarded depending on the employed RAFT agent concentration with no significant difference between the RAFT polymerization performed in fluid CO 2 and in toluene. Full ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 29 publications
(35 reference statements)
6
43
0
1
Order By: Relevance
“…The percent of functionalization indicated that termination occurred to the extent of about 17%, a value which is little higher than that found by SEC but is in accord with reported data about enhanced termination reactions in scCO 2 . 29 The analysis of PS by IR spectroscopy obtained after 48 h of reaction also gives evidence of the endfunctionalization of the chains by the initiator fragment; signals with medium intensity at 1731 and 1179 cm -1 were assigned to ν(C=O) and ν as (O=C−OEt) of the ester group of the initiator. For comparison, the stretching signals of the pure ethyl 2-bromopropionate were observed at 1740 and 1168 cm -1 .…”
Section: Styrene Polymerization In Scco 2 With Complexes 1 and 2 As Cmentioning
confidence: 95%
See 3 more Smart Citations
“…The percent of functionalization indicated that termination occurred to the extent of about 17%, a value which is little higher than that found by SEC but is in accord with reported data about enhanced termination reactions in scCO 2 . 29 The analysis of PS by IR spectroscopy obtained after 48 h of reaction also gives evidence of the endfunctionalization of the chains by the initiator fragment; signals with medium intensity at 1731 and 1179 cm -1 were assigned to ν(C=O) and ν as (O=C−OEt) of the ester group of the initiator. For comparison, the stretching signals of the pure ethyl 2-bromopropionate were observed at 1740 and 1168 cm -1 .…”
Section: Styrene Polymerization In Scco 2 With Complexes 1 and 2 As Cmentioning
confidence: 95%
“…Other studies of polymerization in scCO 2 have been reported using RAFT and SFRP methodologies. 26,29 In Table 1, we summarize the results obtained in three preliminary polymerizations in scCO 2 .…”
Section: Styrene Polymerization In Scco 2 With Complexes 1 and 2 As Cmentioning
confidence: 99%
See 2 more Smart Citations
“…94 However, fairly extensive data have indicated that for peroxide initiators, the rate of initiator decomposition is only marginally affected, if at all, by scCO 2 (relative to n-heptane). 83 Homogeneous RAFT polymerization of S 95 and methyl acrylate 96 have been carried out in scCO 2 , resulting in a somewhat narrower main peak of the MWD than in toluene in the case of S. 95 This was proposed to be the result of an increase in the rate of addition of propagating radicals to RAFT end groups due to the lower viscosity (i.e., assuming this reaction step to be diffusion-controlled), which would in turn give a higher number of activation-deactivation cycles. Homogeneous iodide-mediated polymerization of vinylidene fluoride has also been carried out successfully in scCO 2 .…”
Section: As Polymerization Mediummentioning
confidence: 99%